1998
DOI: 10.1093/humrep/13.2.445
|View full text |Cite
|
Sign up to set email alerts
|

Human endometrial perfusion after tubal occlusion

Abstract: We examined variations in human endometrial microvascular perfusion across one menstrual cycle in women who had undergone tubal ligation and did not report unusual menstruation. Endometrial red blood cell flux was monitored by laser Doppler fluxmetry via a fibreoptic probe atraumatically inserted transvaginally into the uterus of each of 13 conscious volunteers. The observations obtained have been compared with those previously reported from a matched control group of women [B.J. Gannon et al., Hum. Reprod., 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Verco et al [16] evaluated human endometrial microvascular perfusion in women who have undergone TL. They reported that menstrual changes in women after TL were a result of altered endometrial perfusion.…”
Section: Commentmentioning
confidence: 99%
“…Verco et al [16] evaluated human endometrial microvascular perfusion in women who have undergone TL. They reported that menstrual changes in women after TL were a result of altered endometrial perfusion.…”
Section: Commentmentioning
confidence: 99%
“…This is in contrast to the study by Steer et al (11), who found an increased PI value in women with tubal infertility when compared with that of normal women. However, in a subsequent study (12) the investigators found that women who had tubal occlusion exhibited greater endometrial perfusion than the controls.…”
Section: Discussionmentioning
confidence: 90%
“…The more disruptive the tubal blockage, the more intensely vascular anastomosis might be established as a result of the healing process. Furthermore, the counter-current exchange of biological factors may be disturbed either because these factors did not enter the venous drainage or because the arterial supply is unable to deliver these factors to their target organs (12).…”
Section: Discussionmentioning
confidence: 99%
“…The other study (8) showed no significant differences between Pomeroy's technique and laparoscopic tubal rings in terms of post‐sterilization incidence of luteal defects. Verco et al (28) examined variations in human endometrial microvascular perfusion across one menstrual cycle in women who had undergone tubal ligation and reported that the menstrual changes in women after tubal ligation are a consequence of altered endometrial perfusion.…”
Section: Discussionmentioning
confidence: 99%